2014
DOI: 10.3171/2014.9.focus14504
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine enhances temozolomide cytotoxicity in malignant gliomas by blocking autophagy

Abstract: Object In a recent clinical trial, patients with newly diagnosed glioblastoma multiforme benefited from chloroquine (CQ) in combination with conventional therapy (resection, temozolomide [TMZ], and radiation therapy). In the present study, the authors report the mechanism by which CQ enhances the therapeutic efficacy of TMZ to aid future studies aimed at improving this therapeutic regimen. Methods Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
124
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(127 citation statements)
references
References 41 publications
3
124
0
Order By: Relevance
“…Apoptosis and autophagy are closely intertwined processes and the shift apoptosis/autophagy is extremely delicate and highly dependent on metabolic interactions [33]. Previously, we reported that Pyr (as TMZ and other chemotherapeutic drugs) is able to induce autophagy at the early stage of treatment of tumor cells [33, 47, 48]. In this context, the Food and Drug Administration (FDA) have currently approved the use of CQ in combination with conventional therapies to counteract the mechanisms of cell survival in cancer treatment (source http://www.fda.gov).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptosis and autophagy are closely intertwined processes and the shift apoptosis/autophagy is extremely delicate and highly dependent on metabolic interactions [33]. Previously, we reported that Pyr (as TMZ and other chemotherapeutic drugs) is able to induce autophagy at the early stage of treatment of tumor cells [33, 47, 48]. In this context, the Food and Drug Administration (FDA) have currently approved the use of CQ in combination with conventional therapies to counteract the mechanisms of cell survival in cancer treatment (source http://www.fda.gov).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the Food and Drug Administration (FDA) have currently approved the use of CQ in combination with conventional therapies to counteract the mechanisms of cell survival in cancer treatment (source http://www.fda.gov). Therefore, based primarily on the ability to inhibit autophagy, CQ and its derivative, hydroxychloroquine, are currently being investigated as adjuvant therapy in multiple clinical trials for cancer treatment [47], leading to their use as potential chemotherapy and radiotherapy sensitizers rather than antineoplastic. In agreement with these findings, when we combined CQ with Pyr, we found an enhanced cytotoxic effect and block of the autophagic flux.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the existing studies addressing the effects of CHQ in glioma cells have used conventional serum-dependent cell lines that lack stemness properties and/or poorly recapitulate characteristic features of human GBs. For example, the human glioma cell line U87MG, which has been widely used as an experimental model for investigating biological responses mediated by CHQ (21, 22, 29, 30, 81, 82) does not reproduce certain characteristic traits of GBs such as an invasive tumor phenotype, intra-tumoral heterogeneity and high degree of intrinsic radio-resistance. Considering that GSCs are fundamentally distinct from non-stem glioma cells, it is conceivable that their responses to CHQ might also differ from those operating in the latter ones.…”
Section: Chloroquine As Potential Anti-cancer Drug: Unsolved Questionmentioning
confidence: 99%
“…Due to its chemical properties as a weak base, it can inhibit H+-ATPase to increase the lysosomal pH, thus inhibiting enzymatic activity of lysosomal hydrolases and preventing the fusion of autophagosome and lysosome for lysosomotropic properties [18, 19]. Now, several studies have reported that chloroquine could enhance the efficiency of present tumor therapies in many cancers [20-23]. Qin et al [20] found that chloroquine enhanced the efficacy of cisplatin in human adrenocortical carcinoma treatment by blocking autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…Qin et al [20] found that chloroquine enhanced the efficacy of cisplatin in human adrenocortical carcinoma treatment by blocking autophagy. In addition, Golden et al [23] suggested that chloroquine blocked autophagy and triggered endoplasmic reticulum stress, thereby increasing the chemosensitivity of glioma cells to temozolomide. In addition, Ye et al [21] showed that chloroquine enhanced the radiosensitivity of glioma initiating cells.…”
Section: Introductionmentioning
confidence: 99%